Faces are not always special for attention: Effects of response–relevance and identity. (December 2021) - Forster, Sophie; Lavie, Nilli
Highlights: The roles of load and task-relatedness established in a face-name distractor paradigm. Interference from irrelevant famous face distractors depends on perceptual load. Famous faces can only break through demanding non-face tasks when task related. Abstract: Research over the past 25 years indicates that stimulus processing is diminished when attention is engaged in a perceptually demanding task of high 'perceptual load'. These results have generalized across a variety of stimulus categories, but a controversy evolved over the question of whether perception of distractor faces (or other categories of perceptual expertise) can proceed irrespective of the level of perceptual load in the attended task. Here we identify task-relevance, and in particular identity-relevance, as a potentially important factor in explaining prior inconsistencies. In four experiments, we tested whether perceptual load in an attended letter or word task modulates the processing of famous face distractors, while varying their task-relevance. Distractor interference effects on task RTs was reduced by perceptual load not only when the faces were entirely task-irrelevant, but also when the face gender was task relevant, within a name gender classification response-competition task, using famous female or male distractor faces. However, when the identity associated with the famous faces was primed by the task using their names, as in prior demonstrations that face distractors are immune to the effects of perceptual load, we were able to replicate these prior findings. Our findings demonstrate a role for identity-priming by the relevant task in determining attentional capture by faces under high perceptual load. Our results also highlight the importance of considering even relatively subtle forms of task-relevance in selective attention research.